(untitled) (Andamios, Revista de Investigación Social, 2015)
There is a dichotomy in social sciences between positivist models —related to scientific explanations— and models that influence the particularity and comprehension of social phenomena. In this paper, we analyze the contributions made by Schütz, Berger and Habermas to the debate about the objectivity of knowledge. Schütz and Berger analyze society by close approaching and understanding, from the inside, the social phenomena, which permeates their proposal with certain inherent subjectivity. On the other hand, Habermas, with his Theory of Communicative Action, contributes to a vision that is closer to the Verstehen concept, although he surpasses it through the analysis of objectivity as part of inter-subjectivity.